Some observations concerning painted pottery in Moesia superior - Tapavički-Ilić, Milica (Rei Cretariae Romanae Fautorum Acta, 2012)
The first appearance of painted pottery in the territory of what was to become the Roman province of Moesia Superior can be connected with the Scordiscian population. this type of pottery was developed during the 1st century BC by applying technological methods that were taken over from Greek-Hellenistic pottery.